2016
DOI: 10.4103/0974-2727.180790
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Tendency for Thrombosis in Gestational Diabetes Mellitus?

Abstract: Context:Impact of gestational diabetes mellitus (GDM) on the coagulation system, dynamics involved at a pathophysiological level and the exact mechanism remain unclear.Aims:To evaluate the association between diabetes-related parameters and hemostatic factors to search for a tendency of thrombosis in GDM.Settings and Design:Nineteen pregnant women who had GDM, 16 healthy pregnant and 13 healthy nonpregnant controls admitted to the Endocrinology outpatient clinics were enrolled in the study.Subjects and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…They also found that GDM is associated with higher TAT complex, and lower protein C and S compared to normal pregnancy. Gorar et al [20] in 2016 reported higher PAI-1 and lower tPA in GDM compared to control groups, but the results were not significant statistically. Overall, the results of prior studies are quite ambiguous to interpret.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They also found that GDM is associated with higher TAT complex, and lower protein C and S compared to normal pregnancy. Gorar et al [20] in 2016 reported higher PAI-1 and lower tPA in GDM compared to control groups, but the results were not significant statistically. Overall, the results of prior studies are quite ambiguous to interpret.…”
Section: Discussionmentioning
confidence: 97%
“…However, with commonly encountered pathologies during pregnancy, a more pronounced exacerbation of this hypercoagulable profile is documented. [20,21] We designed this retrospective observational cohort study to investigate the trimester specific reference range for DD throughout normal pregnancy, and to compare the distribution of DD in third trimester healthy pregnancies and those complicated by PE, SPE, GDM, PROM, and PPROM. In addition, we aimed to determine the diagnostic value of DD in PE and SPE.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of diabetes enhances the activation of platelets and coagulation factors [12]. It was reported that the levels of prothrombin time and activated partial thrombin time of GDM patients were signi cantly lower than those of the non-pregnant group and healthy pregnancy group, whereas brinogen and plasminogen levels in GDM patients were markedly increased [13]. Here, we found that alpha-2-macroglobulin (A2MG) and brinogen alpha chain (FIBA) were down-regulated in the GDM group.…”
Section: Discussionmentioning
confidence: 99%
“…T2D is associated with a hypercoagulable state, and patients with T2D are at a high risk of atherothrombotic events ( 15 , 16 ). Hyperglycemia, an extrinsic hallmark of T2D, together with dyslipidemia, obesity, aging, pregnancy, surgery and trauma may play a major role in the formation of a hypercoagulable state ( 17 , 18 , 19 ). Hyperglycemia was reported to be involved in the platelet activation, leukocyte aggregation, microparticles formation, endothelial dysfunction, impaired plaque remodeling, activation of coagulation and decreased fibrinolytic activity ( 20 ).…”
Section: Discussionmentioning
confidence: 99%